How Do the Indonesian Pre-service Teachers Perceive CEFR? - Cakrawati, Titis Dewi; Agung, Antonius Setyawan Sugeng Nur; Nugroho, Arif; Ramadhan, Rizki (IJET (Indonesian Journal of English Teaching), 2024)
The Common European Framework of Reference (CEFR) provides a basis for developing language education curriculum, conducting language learning and teaching, and administering language assessment. In the Indonesian context, the recently launched Kurikulum Merdeka refers to the CEFR in targeting the English Proficiency levels that should be achieved in English Subject across different schooling levels. Hence, teachers’ understanding and perceptions of the framework become important. This study aimed to examine the pre-service EFL teachers’ perception of the CEFR. A survey using a 5-point Likert Scale questionnaire and semi structured interviews were conducted to collect both quantitative and qualitative data from 49 pre-service EFL teachers who were selected through a random sampling technique. The results showed that the participants had positive perceptions of the CEFR but they had limited to a moderate understanding level of the CEFR. They only received limited CEFR exposure from a course in their teacher training program. They also mostly associated the CEFR with standardized testing and language certification without understanding the underlying principles of the framework. More comprehensive CEFR training for teacher candidates should be considered before Kurikulum Merdeka is compulsorily implemented. Also, the research can play a crucial role in shaping language education by influencing curriculum development, teacher training, policy decisions, quality assurance measures, student outcomes, and ongoing professional development within the field.